2019
DOI: 10.1590/1981-22562019022.190095
|View full text |Cite
|
Sign up to set email alerts
|

Profile of aggressors of older adults receiving care at a geriatrics and gerontology reference center in the Distrito Federal (Federal District), Brazil

Abstract: Objective: To profile aggressors of older adults who receive care at a reference center in geriatrics and gerontology in the Distrito Federal (Federal District), Brazil, from 2008 to 2018. Method: A retrospective, documentary, descriptive study with a quantitative approach was performed, based on information obtained from the minutes book of the unit, which contained a record of mediation meetings of cases of conflict and violence against older adults, carried out by social workers, nurses and other members of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 9 publications
(11 reference statements)
1
3
0
9
Order By: Relevance
“…The predominance of neglect/abandonment (33.13%) and psychological/moral violence (24.97%) reaffirms the findings of Matos et al 14 who identified (56%) of cases of neglect and (21%) of abandonment in a study carried out at a reference center in geriatric and gerontological health at Distrito Federal. In a literature review 15 , the most common types of violence identified by the authors were the psychological, physical, and financial ones.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The predominance of neglect/abandonment (33.13%) and psychological/moral violence (24.97%) reaffirms the findings of Matos et al 14 who identified (56%) of cases of neglect and (21%) of abandonment in a study carried out at a reference center in geriatric and gerontological health at Distrito Federal. In a literature review 15 , the most common types of violence identified by the authors were the psychological, physical, and financial ones.…”
Section: Discussionsupporting
confidence: 84%
“…The literature points out that the higher frequency of aggressions in households also observed in the present study may be due to the shock of generations imposed by living together, permeated by disputes over physical space, financial difficulties, and lack of knowledge about the aging process and changes caused by the same. Besides, it is noteworthy that in our country (28%) of the homes have at least one old person and (90%) of them live with their close family members 14 .…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Quanto ao perfil do agressor, estudos (10,11) mostram que o agressor normalmente é um membro da família ou pessoas muito próximas ao idoso, do sexo masculino, adultos/ adulto jovem representado por netos e sobrinhos. Existe uma maior prevalência entre os que são desempregados, alcoolista e ou dependente de outras drogas ilícitas, dependente do idoso financeiramente ou emocionalmente, normalmente apresenta um histórico familiar de violência e reside com o idoso na mesma casa ou próximo.…”
Section: O Isolamento Social E Sua Relação Com a Violência Contra Idosos Em Tempos De Pandemiaunclassified
“…No Brasil, 28% dos lares possuem pelo menos um idoso, e os principais agressores são os filhos e os cônjuges 5,6 . A estrutura da família contemporânea, na qual há a inserção da mulher no mercado de trabalho, menor número de filhos e maior número de divórcios contribuem para a marginalização do idoso e ocorrência de violência 2,5 , em contrapartida, a família representa a principal rede de apoio da pessoa idosa, sendo uma instituição concreta de referência, conforme a legislação brasileira 7 .…”
Section: Introductionunclassified